2023
DOI: 10.3390/nu15153495
|View full text |Cite
|
Sign up to set email alerts
|

Indicaxanthin Induces Autophagy in Intestinal Epithelial Cancer Cells by Epigenetic Mechanisms Involving DNA Methylation

Abstract: Autophagy is an evolutionarily conserved process critical in maintaining cellular homeostasis. Recently, the anticancer potential of autophagy inducers, including phytochemicals, was suggested. Indicaxanthin is a betalain pigment found in prickly pear fruit with antiproliferative and pro-apoptotic activities in colorectal cancer cells associated with epigenetic changes in selected methylation-silenced oncosuppressor genes. Here, we demonstrate that indicaxanthin induces the up-regulation of the autophagic mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 89 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…Recently, treatment strategies for OA have been developed that target senescent cells and the paracrine and autocrine secretions of the senescence-associated secretory phenotype [ 102 ]. Our labs have already ascertained the nutrigenomic effects of some molecules contained in plants, highlighting their effects on inflammation and autophagy, and their power to counteract epi-mutagenic actions [ 90 , 103 , 104 , 105 , 106 ], for example, arsenic-induced actions [ 106 ]. We therefore believe that the nutrigenomic approach represents the most modern frontier for understanding the action of flavonoids in OA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, treatment strategies for OA have been developed that target senescent cells and the paracrine and autocrine secretions of the senescence-associated secretory phenotype [ 102 ]. Our labs have already ascertained the nutrigenomic effects of some molecules contained in plants, highlighting their effects on inflammation and autophagy, and their power to counteract epi-mutagenic actions [ 90 , 103 , 104 , 105 , 106 ], for example, arsenic-induced actions [ 106 ]. We therefore believe that the nutrigenomic approach represents the most modern frontier for understanding the action of flavonoids in OA.…”
Section: Discussionmentioning
confidence: 99%
“…The same is said of Indicaxanthin, where we note its properties as a redox agent [26], as a protector against hemolysis [27], and as a pigment capable of crossing the blood-brain barrier when administered in nutritionally relevant quantities [28]. Recent studies have also shown the role of indicaxanthin as a modulator of DNA methylation in Caco2 cells, making this molecule a good candidate for an anticancer drug [12], and its pro-autophagic potential in human colorectal cancer cells [29].…”
Section: Indicaxanthin: the Yellow Pigment Of Prickly Pear Fruitmentioning
confidence: 96%